PENGGUNAAN METODE TANYA JAWAB UNTUK MENINGKATKAN KEBERANIAN MENGEMUKAKAN PENDAPAT PADA ANAK DI TKS PGRI KALIANGET BARAT SUMENEP - Sutrisno, Tri (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2020)
The purpose of the research is a benchmark of all research conducted. The objectives in this study are: (1) Want to know the development of children's courage in improving abilities by using the question and answer method. (2) Want to know the impact of using the question and answer method on children's courage in improving their ability to express their opinions. Based on the results of improved learning about communicating / speaking simply in developing the courage of children to express their opinions in Kalianget Barat TKS. Sumenep. In the first cycle, the highest value achieved by children was 80 as many as 10 children, the lowest value was 20 as many as 4 children and the average grade of 6.46 (67%). While the observation collection of question and answer methods West Kalianget TKS Kab. Sumenep in the first cycle as contained in the observation sheet is known that the teacher uses examples and teaching aids (good), the language used by the teacher is clear and simple (good), the teacher checks the child's understanding by asking questions / giving assignments (good), the teacher gives an opportunity ask questions (enough), children answer questions asked by teachers (enough), logical children's answers (enough), children answer other children's questions (enough), respond by teachers (good), and children discuss (good). In the observations of the first cycle has not shown the active attractiveness of children towards the learning given by the teacher. While in the second cycle the results of improved learning about communicating / speaking simply in developing the courage of children to express their opinions Kalianget Barat TKS Kab. Sumenep. In cycle II, it was found that the highest value achieved by children was 160 by 20 children, and the average grade was 7.9 (75%). While the observation collection of question and answer methods West Kalianget TKS Kab. Sumenep in cycle II as contained in the observation sheet is known that the teacher uses examples and teaching aids (good), the language used by the teacher is clear and simple (good), the teacher checks the child's understanding by asking questions / giving assignments (good), the teacher gives an opportunity ask questions (good), children answer questions asked by teachers (good), logical children's answers (enough), children answer other children's questions (good), responded by teachers (good), and children discuss (good). In observation of the second cycle of learning is smooth and produces a level of completeness that exceeds the target.